How to improve hospital employees' health and well-being: a staff consultation - Wendy Lawrence; Jasmine Hine; Daniella Watson; Julia Smedley; Karen Walker-Bone (BMC, 2022)
Abstract Objective Explore perspectives from healthcare workers in a large public hospital (11,000 staff) on employers supporting their health and well-being. Methods Heads of departments/services were invited to convene focus groups, facilitated by a moderator using a semi-structured discussion guide.  Results Over 450 members of staff participated in 28 focus groups. Themes identified were: 1)unique nature of working in a large hospital, 2)hospital management agenda and relationship with staff, 3)working environment, and 4)staff health and well-being initiatives. Conclusions Optimal uptake of health-promoting initiatives was hindered in part due to lack of staff awareness and a range of barriers. Key requirements for improving staff health were perceived to be sufficient staffing, time and space to work safely and comfortably. Engaging with staff to hear their views, build trust and identify their needs is an essential first step.